THE STYLE OF SPEECH IN THE VIEWS OF THE ENLIGHTENERS - Rukhsora Khalilova Raupovna (Bright Mind Publishing, 2025)
When a person uses speech, he means not only talking about the current situation, but also that what he says should make an impression, have a certain impact, and have an effect, which are forms of introducing society to language culture, forming a careful attitude towards language, and consciously mastering language as a means of communication.
Keywords: Speech, education, pedagogy, rhetoric, speech style, teachers, individual speech, eloquence, communication.